The Professional Criteria necessary for Research Article to be Published in Studies on Arabic Language and Literature - Sadeq Askari (دراسات في اللغة العربيّة وآدابها)
There is little doubt that awareness of professional criteria and the characteristics of good research reports are of crucial importance to those interested in publishing research articles. This is so because following such criteria is the only way to create scientific innovations. Experts have mentioned many criteria for the choice of topic, preparing the sections and subsections, and providing the results of the analyses. This article use the descriptive-analytical method to provide the criteria and guidelines referred to in reviewing articles submitted to Studies on Arabic Language and Literature. The result of this research shows that most research articles suffer from lack of critical thinking which, in turn, stems from lack of experience. So, it is important that the researchers become familiar with critical criteria, which can be summarized as follows: choice of specific topics, clarity and shortness of the tile, identifying and discussing the different dimensions of the topic, sticking to a logical progression, exploring as much existing related literature as practical, considering the value and validity of the sources, identifying and categorizing different views to convince the audience as to the soundness of the authorâs view.